Otimização de atividades críticas de parques eólicos: redução de custos através de modelagem de logística, cronograma, manutenção, pavimentação e concretagem - Bluhm, Bruno Bezerra (2017)
Aiming to obtain cost reduction in wind farm construction projects, this study presents the conception and utilization of new civil works optimization initiatives, by creating specific modelling of critical activities. This theme is particularly relevant in Brazil, for the wind sector has presented a steady growth in the past decade, construction productivity indicators present historic low levels and there is considerable margin in applying infrastructure academic studies in new wind farm projects. This dissertation has been applied in six recently built Brazilian wind farms, with more than 1,4GW of installed capacity. The modelled activities are: layout project; construction planning; roads and pads paving; foundations concrete pouring; and heavy equipment maintenance policy. These activities have been identified as critical using a work breakdown structure approach. First implementation tests obtained financial gains such as: reduction of 53 thousand km in concrete truck routing; 20% less field time for the foundation, steeling and concrete teams; root cause identification for issues in dump truck performance; 25% cost reduction in concrete transport; and creation of optimal maintenance policies depending on local geographies. Continuing these initiatives in new projects has the potential to further enhance wind energy’s position as a technically and financially feasible energy alternative for Brazil.